EXPLORING THE LEVEL OF STUDENTS’ SELF-EFFICACY IN SPEAKING CLASS - Agung, Antonius Setyawan Sugeng Nur; Quinones, Charito A; Siboro, Efrika (LLT Journal: A Journal on Language and Language Teaching, 2022)
Exploring the level of the students’ self-efficacy toward their speaking ability is the grand design of this study. The participants of this study were 28 non-native students from the suburban area in West Borneo. Those students belong to the third semester of the speaking class. In collecting the data, they were given a questionnaire. An in-depth interview was also conducted with 3 prominent students to validate and triangulate the represented data in the questionnaire result. Adopting Bandura’s theory, the results of this study show that the students manifested slightly high self-efficacy in the magnitude dimension, slightly high self-efficacy in the generality dimension, and very high self-efficacy in the strength dimension. In addition, the in-depth interview affirms that the students’ level in magnitude is influenced by their educational background; the students’ level in generality is affected by their interests in their particular field, and the student's level of strength is determined by their strong belief.